2009
DOI: 10.1177/0730888409341358
|View full text |Cite
|
Sign up to set email alerts
|

Grounding the Regime of Precarious Employment

Abstract: This ethnography of day laboring contends that to better understand how the labor process situated within the industry is regulated at the micro-level, it is necessary to move beyond studies that limit their analyses of homeless day laborers—an important subset of workers who mediate and respond to this low-road industry's bottom line imperatives—to worker grievances or the strategies they use to combat anonymity. This article shows that the reasons homeless workers see day labor as a “sensible” income-generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 24 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…So connectivity between country of origin home-life and networks can limit labour market progression for migrants (MacKenzie and Forde, 2009). Intermediaries and wider social networks can contribute to the (exclusion and marginalization) difficulties precarious workers face in securing better jobs in either formal or informal employment (McCollum and Findlay, 2015: 430;Williams, 2009). However, the authority of this view is contested and precarious migrants may not be merely passive victims of their position in the market for bad jobs; rather they can use informal networks to promote job mobility and build skills to escape such jobs (Alberti, 2015;Hagan et al, 2011).…”
Section: Analytical and Theoretical Contributionmentioning
confidence: 99%
“…So connectivity between country of origin home-life and networks can limit labour market progression for migrants (MacKenzie and Forde, 2009). Intermediaries and wider social networks can contribute to the (exclusion and marginalization) difficulties precarious workers face in securing better jobs in either formal or informal employment (McCollum and Findlay, 2015: 430;Williams, 2009). However, the authority of this view is contested and precarious migrants may not be merely passive victims of their position in the market for bad jobs; rather they can use informal networks to promote job mobility and build skills to escape such jobs (Alberti, 2015;Hagan et al, 2011).…”
Section: Analytical and Theoretical Contributionmentioning
confidence: 99%
“…So there are different types of migrant labour employed in HCWs. Some are reliant on intermediaries and wider social networks for employment which can confine precarious workers to less good jobs in either formal or informal employment (McCollum and Findlay : 430; Williams ). We found that a permissive UK legal environment created a ‘sub‐contract’ labour market populated by precarious and vulnerable labour unsure if they are an employee and who may not know the identity of their employer (Wills et al .…”
Section: Researching Employment Relations In Hand Car Washesmentioning
confidence: 99%